2023
DOI: 10.17085/apm.23041
|View full text |Cite
|
Sign up to set email alerts
|

What we need to know and do on sugammadex usage in pregnant and lactating women and those on hormonal contraceptives

Abstract: Sugammadex is a chemically modified γ-cyclodextrin that is used as a selective reversal agent for steroidal neuromuscular blockade. The use of sugammadex has greatly increased globally; however, little is known about its potential adverse effects in pregnant and lactating women or those using hormonal contraceptives. There are three important theoretical assumptions. Firstly, pregnancy-related physiological changes involve most organs and affect the pharmacokinetic profiles of medications. Considering the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Do and Cho, 7 recently addressed three potential adverse effects of SGX in pregnant and lactating women, and in patients using hormonal contraceptives: (a) pregnancy-related physiologic changes affecting the pharmacokinetic profile of drugs and alterations in dosage and safety profile of SGX; (b) the large polarized SGX is expected to have limited placental transfer to the fetus and limited excretion in breast milk; and (c) cyclodextrins are known to form inclusion complexes with other compounds, such as progesterone, potentially reducing progesterone levels and influencing reproductive potential, such as early cessation of pregnancy and failure of hormonal contraception. Their narrative review confirmed that preterm births and miscarriages within four weeks of the administration of SGX during non-obstetric interventions, were not significantly different between patients with or without SGX exposure and no patient experienced preterm delivery or labor induced by SGX administration 7 . Awaiting further evidence, it may be acceptable to use SGX during lactation and breastfeeding, although the infants’ immature metabolism and renal function may delay SGX clearance and warrants its cautious use.…”
Section: Commentmentioning
confidence: 99%
“…Do and Cho, 7 recently addressed three potential adverse effects of SGX in pregnant and lactating women, and in patients using hormonal contraceptives: (a) pregnancy-related physiologic changes affecting the pharmacokinetic profile of drugs and alterations in dosage and safety profile of SGX; (b) the large polarized SGX is expected to have limited placental transfer to the fetus and limited excretion in breast milk; and (c) cyclodextrins are known to form inclusion complexes with other compounds, such as progesterone, potentially reducing progesterone levels and influencing reproductive potential, such as early cessation of pregnancy and failure of hormonal contraception. Their narrative review confirmed that preterm births and miscarriages within four weeks of the administration of SGX during non-obstetric interventions, were not significantly different between patients with or without SGX exposure and no patient experienced preterm delivery or labor induced by SGX administration 7 . Awaiting further evidence, it may be acceptable to use SGX during lactation and breastfeeding, although the infants’ immature metabolism and renal function may delay SGX clearance and warrants its cautious use.…”
Section: Commentmentioning
confidence: 99%